Psychological intervention in crisis by telephone - Pereira, Ana Filipa Tavares (2020)
In Portugal, the psychological intervention in crisis and emergencies, by telephone, is ensured in a pre-hospital setting by psychologists from the Center for Psychological Support and Crisis Intervention (CAPIC). This study endeavors to demonstrate the intervention of CAPIC´s psychologists in the Dispatch and Guidance Center for Urgent Patients (CODU) through the analysis of data registered in CAPIC Software from 2013 to 2018 in overall 50226 situations recorded. Through a Multiple Correspondence Analysis (MCA), we pretended to identify possible profiles in the space defined by a set of categorical variables associated to the symptoms as well as the type of occurrence, gender, and the intervention of the psychologist through referral, in an effort to investigate the multiple relationships that are possible to establish between them in the context of interdependence. It was possible to identify two dimensions, namely dimension 1, composed of indicators of “symptomatology” and dimension 2 that essentially points to “characteristics of the event”, demonstrating a common intentional sharing between the variables. However, it was the symptomatology that seems to have the greatest contribution in explaining the data. Owing to its unique and innovative character, this study can be considered a pioneer, contributing to the knowledge of the role of the psychologist in the Emergency Medical Center. Therefore, there is a need for more research that can deepen this theme, since worldwide no similar reality is known. Some limitations relate to the characteristics of the computer software used, which may lead to less objective data. In order to evaluate the success of the intervention, the introduction of other variables is suggested.